2018 13th IEEE International Conference on Automatic Face &Amp; Gesture Recognition (FG 2018) 2018
DOI: 10.1109/fg.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Facial Parts Localization and Deep Learning for 3D Facial Expression Recognition

Abstract: Meaningful facial parts can convey key cues for both facial action unit detection and expression prediction. Textured 3D face scan can provide both detailed 3D geometric shape and 2D texture appearance cues of the face which are beneficial for Facial Expression Recognition (FER). However, accurate facial parts extraction as well as their fusion are challenging tasks. In this paper, a novel system for 3D FER is designed based on accurate facial parts extraction and deep feature fusion of facial parts. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…Features are usually calculated on the region surrounding principal facial landmarks or on the mouth and eyes that inherently contain essential information for emotion recognition. These key features that are considered closely related to expression categories, in order to perform FER are fed to various classifiers, as well as Support-Vector Machines (SVM) [47][48][49][50][51], Adaboost, k-Nearest Neighbors (k-NN), Linear Discriminant Analysis (LDA), Modified Principal Component Analysis (PCA), Hidden Markov Model (HMM) [44][45][46], Random Forest [52] or Neural Networks [51,53,54].…”
Section: Feature-based Vs Model-based Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Features are usually calculated on the region surrounding principal facial landmarks or on the mouth and eyes that inherently contain essential information for emotion recognition. These key features that are considered closely related to expression categories, in order to perform FER are fed to various classifiers, as well as Support-Vector Machines (SVM) [47][48][49][50][51], Adaboost, k-Nearest Neighbors (k-NN), Linear Discriminant Analysis (LDA), Modified Principal Component Analysis (PCA), Hidden Markov Model (HMM) [44][45][46], Random Forest [52] or Neural Networks [51,53,54].…”
Section: Feature-based Vs Model-based Algorithmsmentioning
confidence: 99%
“…Savran et al [33] showed that in general 3D data perform better than 2D data, especially for lower face AUs, but with the fusion of two modalities higher detection rates are achieved (97.1 %). Depth maps (3D meshes) are fused with other 2D maps, such as texture maps [2,51,107], curvature maps [2,108] and normal maps [2,107].…”
Section: B 3d Fermentioning
confidence: 99%
See 2 more Smart Citations
“…Jan et.al [4] suggested that an accurate location of facial components and profound teaching for identification of 3D facial expression using techniques. In this paper a new scheme for 3D facial recognition is intended based on precise facial components removal as well as their combination are difficult duties depending on parameters of texture, facial parts 3 dimensions and its outcomes in that the suggested method image 3D facial recognition offers an efficient identification of facial parts and textures and the benefit of this strategy or study that accurate recognition of facial parts can be done.…”
Section: An Separation Of Different Facial Expression Recognition Systemmentioning
confidence: 99%